Nanoscale spheroidized cementite induced ultrahigh strength-ductility combination in innovatively processed ultrafine-grained low alloy medium-carbon steel - N. Jia (Nature Portfolio, 2017)
Abstract We describe here innovative processing of low alloy medium-carbon steel with a duplex microstructure composed of nanoscale spheroidized cementite (Fe3C) in an ultrafine-grained (UFG) ferritic steel. After multi-pass rolling and intermittent annealing at 550 °C for 300 s, the obtained UFG-1 steel showed an average ferrite grain size of ~430 nm, containing nanoscale spheroidized cementite (Fe3C) particles with an average size of ~70 nm. On annealing at 600 °C for 300 s, the average size of ferritic grains was increased to ~680 nm and the average size of spheroidized Fe3C particles increased to ~90 nm, referred as UFG-2 steel. Tensile tests indicated that UFG-1 steel had high yield strength (σ y) of 1260 MPa, and ultimate tensile strength (σ UTS) of 1400 MPa. These values are higher than that of UFG-2 steel (σ y = 1080 MPa and σ UTS = 1200 MPa), suggesting that the strengthening contribution is a cumulative effect of decrease in ferrite grain size and nanoscale cementite. The incoherent interfaces between nanosized particles and the matrix acted as a strong barrier to dislocation motion. The study underscores that nanosized precipitates not only provide strength but also contribute to ductility, which is very encouraging for improving the ductility of medium-carbon steels.